Planning for Developing Urban Tourism Destinations (Study at the Tourism Office of Kupang City) - ADOE, Eurike F D; FANGGIDAE, Apriana H. J.; TODA, Hendrik (Journal of Tourism Economics and Policy, 2024)
Tourism management in Kupang City requires significant attention from the local government due to its current low income from this sector. Given the city's promising tourism potential, it can be a vital avenue to boost local revenue, enhance the community's economy, and foster regional development. This qualitative research involved primary and secondary data sources collected via observation, interviews, and document searches with 40 informants. The data were analyzed using Creswell's (2016) methodology. Findings indicate that: (a) Both official and unofficial actors are involved in planning; (b) Economic reviews identify community mindset as a threat, economic development as an opportunity, budget constraints as a weakness, and the city's status as the provincial capital and gateway to Timor Leste as strengths; (c) Current tourism is limited to natural sites, with urban tourism development not yet optimal; (d) Goals and strategies are aligned with the city's vision and mission, requiring communication between stakeholders and the community; (e) The Kupang City Tourism Office is still developing the city tourism development plan.